2010
DOI: 10.4067/s0717-95022010000400037
|View full text |Cite
|
Sign up to set email alerts
|

Gross and Histologic Evaluation of Abdominal Adhesions Associated with Chromic Catgut and Polypropylene Sutured Enteropexies in Dog

Abstract: The gross and histologic patterns of abdominal adhesions formed by the use of chromic catgut and polypropylene suture materials were evaluated in dogs. Gross and histologic examinations did not reveal significant difference (p>0.05) in the degree of adhesions observed at enteropexy sites in both suture materials. The use of polypropylene with superior suture qualities should be considered instead of chromic catgut for procedures in which adhesion is desired in the dog.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 10 publications
1
2
0
Order By: Relevance
“…The extensive adhesion response in animals submitted to hysterorrhaphy with catgut has been attributed to the inflammatory reaction to the suture wire type, which has been corroborated by similar observations in urinary bladder suturing of rats . Lymphocyte predominance in the catgut group, in comparison with the control group, may be explained by its action for up to 120 h in a normal inflammatory process; this justifies the presence of adhesions during the remodeling phase in inflammatory events with the formation of fibrinogen‐rich exudates …”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…The extensive adhesion response in animals submitted to hysterorrhaphy with catgut has been attributed to the inflammatory reaction to the suture wire type, which has been corroborated by similar observations in urinary bladder suturing of rats . Lymphocyte predominance in the catgut group, in comparison with the control group, may be explained by its action for up to 120 h in a normal inflammatory process; this justifies the presence of adhesions during the remodeling phase in inflammatory events with the formation of fibrinogen‐rich exudates …”
Section: Discussionsupporting
confidence: 57%
“…8 Lymphocyte predominance in the catgut group, in comparison with the control group, may be explained by its action for up to 120 h in a normal inflammatory process 9 ; this justifies the presence of adhesions during the remodeling phase in inflammatory events with the formation of fibrinogen-rich exudates. 10 Chitosan, poly [(1,4)-D-glucose-2-amine], (C 6 H 11 IN 4 ) n , is the deacetylated form of chitin (polysaccharide mainly found in crustaceans, insects, fungi, and algae exoskeleton). The use of chitosan in sutures is of interest because it has very low toxicity and complete biodegradation.…”
Section: Discussionmentioning
confidence: 99%
“…Intestinal plication (or enteropexy), as is also defined experimentally produces significant morbidity, resulting in vomiting, diarrhea, anorexia, constipation, obstruction, adhesions, perforation and septic peritonitis, especially after a month of surgery [18]. Research with enteropexy execution in dogs observed a gradual increase of adhesions from seven to 30 days after surgery [1].…”
Section: Introductionmentioning
confidence: 99%